2007
DOI: 10.1108/10595420710844316
|View full text |Cite
|
Sign up to set email alerts
|

The internet and international marketing

Abstract: Purpose -This paper aims to provide a link between the concepts of internationalization and intemetalization, since both have become an e-business. Design/methodology/approach -This study extends a model developed by Buttriss and Wilkinson which offers a starting-point for classifying elements and identifying interactions in the internationalization process in global marketing. The objective has been achieved through the comparison between the Buttriss and Wilkinson model and a suggested model by the researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
2
0
2
Order By: Relevance
“…This implies that e-commerce has positive impact on service operations. This result agrees with Alrawi, (2007) who asserted that that ecommerce have changed the way of delivering the product and consumers can have more choices than they could easily locate otherwise and transaction can be made 24 hours a day, from almost any location. Result also revealed that e-commerce adoption by supermarkets has significant impact on cost reduction with (β = 0.348; t = 0.121) at 5% level.…”
Section: Model Specificationsupporting
confidence: 89%
See 1 more Smart Citation
“…This implies that e-commerce has positive impact on service operations. This result agrees with Alrawi, (2007) who asserted that that ecommerce have changed the way of delivering the product and consumers can have more choices than they could easily locate otherwise and transaction can be made 24 hours a day, from almost any location. Result also revealed that e-commerce adoption by supermarkets has significant impact on cost reduction with (β = 0.348; t = 0.121) at 5% level.…”
Section: Model Specificationsupporting
confidence: 89%
“…8 ISSN: 2222 219 www.hrmars.com business transactions for buyers and vendors alike (Buderi, 2005). Alrawi, (2007) affirmed that with e-commerce buyers can access information instantly, and even virtually test the product, which in traditional marketing concept would be time consuming. He said that e-commerce have changed the way of delivering the product, consumers can have more choices than they could easily locate otherwise and transaction can be made 24 hours a day, from almost any location.…”
Section: International Journal Of Academic Research In Business and Smentioning
confidence: 99%
“…ürünler tüketiciye sunulabilir. Bu bağlamda, e-ticaret, ürünün teslimat şeklini bile değiştirebilmektedir (Alrawi, 2007).…”
Section: üRün (Hizmet) (K2)unclassified
“…Bu nedenle, şirketler uygun fiyatlar ve çoklu hizmetler sunarak müşteri memnuniyetini kazanmaya çalışmaktadır (Khalid, Lee, Choi ve Ahn, 2018). Çevrimiçi işletmeler, depolama, üretim, dağıtım ve satışlarının daha iyi koordine edilmesiyle, ürünlerin genel maliyetlerini düşürebilmektedir (Alrawi, 2007). Ayrıca elektronik işlemlerin, telefon ya da kişisel satışlara göre, daha düşük maliyetli olması, fiyat indirimlerini mümkün kılmaktadır (Chaffey, 2002).…”
Section: E-ticaret Alanında Müşteri Memnuniyeti Takibini Etkileyen Faktörlerin Platformunclassified
“…This tallies with what theory suggests on the relationship between ecommerce adoption and service operations. Alrawi (2007) claims that e-commerce enables consumers to have more choices and are able to transact from any location for 24 hours a day. He also indicated that ecommerce has changed the way products are delivered to consumers.…”
Section: Model Specification Used For the Simple Regression Analysismentioning
confidence: 99%